THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND THE PAIN SCALE OF PRIMARY DYSMENORRHEA IN MIDWIFERY STUDENTS - Lara Lostrista; Zakiyatul Faizah (Indonesian Midwifery and Health Sciences Journal, 2026)
Background: Dysmenorrhea is one of the most common gynecological problems, affecting 90% of women worldwide. One of the factors causing primary dysmenorrhea is nutritional status, which can be assessed directly using BMI (Body Mass Index). The purpose of this study was to analyze the relationship between BMI and the primary dysmenorrhea scale in midwifery students at the Faculty of Medicine, Airlangga University, Surabaya. Method: This study used an observational analytical design with a cross-sectional approach on 76 midwifery students from the 2021 cohort and 74 midwifery students from the 2022 cohort at the Faculty of Medicine, Airlangga University, Surabaya. The research data were analyzed using a non-parametric rank correlation test (Spearman). Results: The results showed that 25 midwifery students (21.0%) were underweight, 56 students (47.1%) were normal weight, 15 students (12.6%) were overweight, and 23 students (19.3%) were obese. The results of the Spearman test showed a p-value of 0.045. Conclusion: There was a relationship between BMI (Body Mass Index) and the primary dysmenorrhea pain scale among midwifery students at the Faculty of Medicine, Airlangga University.